A European Union of security and defense : seizing the moment - Lagarto, Beatriz Moura (2019)
Nowadays, the European Union (EU) is facing a completely new security environment that is challenging its capacity to react. In the past, the EU has been shamed several times by the lack of a strong leadership and of strategic vision, which might be changing now. The European project is in a decisive moment, which is reflected in the presentation in June 2016 of “A Global Strategy on the Europeans Union’s Foreign and Security Policy” (EUGS). The EUGS marks the start of a new momentum in the history of European integration with key decisions being finally made. When comparing the last three years with what has been achieved since the 1950s, it is possible to state right away that a lot is indeed being done. However, history shows that integration/cooperation in foreign, security and defence policies has always been marked by great difficulties. It is the aim of this dissertation to study the development of a European Union of Security and Defence, understanding if the courses of action that are being taken will allow for the EU to close the gap between vision and action and finally meet its commitments